UPAYA PENINGKATAN AKTIVITAS BELAJAR FISIKA MELALUI PENERAPAN PEMBELAJARAN COOPERATIVE LEARNING DI SMA NEGERI 3 BUNGO - Despita Despita (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
The aims of the research was to know the increase of physics subject by using cooperative learning in SMA N 3 Bungo. As ungulan school SMA N 3 Bungo has always been consistent in doing increase the learning process in order to increase the competencies of graduates. Various attempts were made as well for the ongoing development of teachers , administrators and all elements of the school .To increase of physics subject is an acceptable way by using cooperative learning. Cooperative learning is a learning model for give a chance for students to make interactions to others. In addition cooperative learning is the best way to apply because every students has give (team reward), (individual aecountability) (equal opportunities for success) that can give motivation for student to increase ability in physics subject and make student interesting of this subject to get the great result in physics learning. As long as, students in SMA N 3 the best students in Physics always has dominate in Physics learning, without give a chance for another students, so that cooperative learning is best choice for Physics study.